The effect of dietary supplementation with globin and spray‐dried porcine plasma on performance, digestibility and histomorphological traits in broiler chickens. (4th May 2020) - Dabbou, Sihem; Trocino, Angela; Xiccato, Gerolamo; Nery, Joana; Madrid, Josefa; Martinez, Silvia; Hernández, Fuensanta; Kalmar, Isabelle D.; Capucchio, Maria Teresa; Colombino, Elena; Biasato, Ilaria; Bailoni, Lucia; et al.
Abstract: This study evaluated the effects of globin and spray‐dried porcine plasma (SDPP) on growth performance, digestibility, nitrogen retention, energy retention efficiency (ERE) and intestinal morphology of broiler chickens. A total of 336‐day‐old male broiler chickens were reared from 1 to 40 days of age and fed 3 diets (8 replicates/diet, 14 birds/replicate) during 3 feeding phases: starter (1–12 days), grower (12–25 days) and finisher (25–40 days). Isonitrogenous diets were formulated by replacing gluten protein isolate contained in the control diet (C diet) with 2% (starter) or 1% (grower and finisher) spray‐dried porcine plasma in the plasma diet (SDPP diet). The globin diet (G diet) was obtained by adding globin on the top of C diet at a dose of 0.08% for the whole rearing period. Total tract apparent digestibility (aD), nitrogen retention and ERE were assessed during the three growing phases. At 12 and 40 days of age, one bird per pen was slaughtered to sample gut, liver, spleen and bursa of Fabricius for histomorphological investigations. The SDPP diet increased body weights of chickens at 12 (+60 g; p < .001), 25 (+101 g; p < .001) and 40 days (+130 g; p = .018) of age compared to C and G diets. Also SDPP improved crude protein aD (+9.7%) and ERE (+12.3%) during the starter phase ( p < .001). Dietary globin and SDPP inclusion did not affect either the gut morphology or the histopathological findings in birds at 12 and 40 days of age, despite a numerical (+6.90% and +7.40% respectively) villus height improvement in the SDPP group. Overall, these results confirm that dietary supplementation with SDPP and, to a lesser extent, with globin can improve growth performance and dietary protein and energy utilization in broiler chickens without effect on gut functionality.